TA Treatment of Depression. A Simplified Hermeneutic Single-Case Efficacy Design. The Case of “Giovanni” - Mariavittoria Zanchetta; Laura Farina; Stefano Morena; Enrico Benelli (International Journal of Transactional Analysis Research, 2019)
This study is inspired by previous case series replications of Hermeneutic Single-Case Efficacy Design which aim was to evaluate the effectiveness of a manualized transactional analysis treatment for depressive disorders and depressive personality. We address problems and difficulties emerged in previous case series, such as: spending time in training a group of people to conduct the hermeneutic analysis, organizing the involvement of external judges to give the final adjudication, and dealing with inconsistencies between quantitative and qualitative data. For these reasons, this study suggests a simplified method to conduct the hermeneutic analysis that require one person only, maintaining its validity. Therefore, we integrated hermeneutic design with the pragmatic case evaluation methodology in order to follow pre-defined criteria in analysing qualitative material. Furthermore, we present a way to use the Script System to detect changes in depressive symptomatology and depressive personality. We tested this approach to HSCED in the case of ‘Giovanni, a 17-years old white Italian boy who attended sixteen session of transactional analysis psychotherapy with a white Italian woman specializing in psychotherapy with 2 years of clinical experience. The patient satisfied DSM-5 criteria for moderate major depressive disorder and generalized anxiety disorder.This is the second investigation which has evaluated the effectiveness of Transactional Analysis psychotherapy for depressed adolescents.